THE INFLUENCE OF BRAND IMAGE AND BRAND TRUST ON CUSTOMER SATISFACTION OF FERTILIZER ON FARMERS IN BANTUL REGENCY - Hijami, Muhammad Fikri; Perwitasari, Hani; Suryantini, Any (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The widely distributed Non-subsidized NPK fertilizers which are quite diverse give more options for farmers to choose from which they want to use in their farming activities. This study aims to determine the effect of brand image and brand trust on customer satisfaction of non-subsidized NPK fertilizer shallot farmers in Bantul Regency. This quantitative research was conducted by using a non-probability sampling method with convenience sampling technique. The number of respondents in this study was 100 shallot farmers who use non-subsidized NPK fertilizer with the Mutiara and Phonska Plus brands at least twice. Data analysis was done with Structural Equation Modelling-Partial Least Square (SEM-PLS). The results of this study shows that the brand image variable is measured from indicators of brand identity, brand personality, brand associations, and brand attitudes and behavior. The brand trust variable is measured by some indicators which are brand characteristics, company characteristics, customer-brand characteristics, affective trust, and cognitive trust. The customer satisfaction variable is measured by service quality, product quality, price suitability, as well as situation and personality. Furthermore, the analysis shows that brand image and brand trust have a positive and significant effect on customer satisfaction. It is expected that farmers can exchange information regarding the use of non-subsidized NPK fertilizer in order to decide best decisions in cultivating shallot plants.